2018
DOI: 10.1007/s00122-018-3054-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a molecular marker tightly linked to bacterial wilt resistance in tomato by genome-wide SNP analysis

Abstract: Genotyping of disease resistance to bacterial wilt in tomato by a genome-wide SNP analysis Bacterial wilt caused by Ralstonia pseudosolanacearum is one of the destructive diseases in tomato. The previous studies have identified Bwr-6 (chromosome 6) and Bwr-12 (chromosome 12) loci as the major quantitative trait loci (QTLs) contributing to resistance against bacterial wilt in tomato cultivar 'Hawaii7996'. However, the genetic identities of two QTLs have not been uncovered yet. In this study, using whole-genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Previous reports showed that Bwr-12 is confined to phylotype I defense response (Carmeille et al 2006a, b;Wang et al 2000Wang et al , 2013. Recently it was reported by Kim et al (2018) that genes encoding leucine-rich repeat (LRR) receptor-like proteins are located in the Bwr-12 region and may be associated with resistance. A dense genetic map with markers flanking and within QTL regions will help to improve the efficiency to breed tomato resistant to BW.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that Bwr-12 is confined to phylotype I defense response (Carmeille et al 2006a, b;Wang et al 2000Wang et al , 2013. Recently it was reported by Kim et al (2018) that genes encoding leucine-rich repeat (LRR) receptor-like proteins are located in the Bwr-12 region and may be associated with resistance. A dense genetic map with markers flanking and within QTL regions will help to improve the efficiency to breed tomato resistant to BW.…”
Section: Discussionmentioning
confidence: 99%
“…Mean values of NILs, the susceptible parent and controls showed different sensitivity patterns depending of the bacterial strain and season. Under higher temperatures (21-30°C) the plant defense response against BW seems to be lower [61][62], while Pss4 and Pss1632 or other tropical strains such as of K60 and GMI1000 have reduced virulence in cooler conditions (18-25°C) [3,[63][64]. Consequently, the percentage of wilted NILs was significantly higher in the relative warm conditions of the autumn trial than in the cool spring trial.…”
Section: Discussionmentioning
confidence: 94%
“…Non-synonymous SNPs between resistant and susceptible groups of tomato cultivars near Bwr-6 within 15 candidate genes (18 SNPs) were previously identified by whole-genome resequencing ( Kim et al 2018 ). Each candidate gene contained one non-synonymous SNP except two genes, Solyc06g051110.1 and Solyc06g051140.2 , which have two and three SNPs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although two QTL, Bwr-6 and Bwr-12 , were repeatedly confirmed as major contributors to bacterial wilt resistance in Hawaii 7996, the genetic nature of these critical QTL remained unidentified. We have previously conducted whole-genome resequencing of two susceptible cultivars (Heinz 1706 and BWS-3) and seven resistant cultivars (Hawaii 7996, Hawaii 7998, 10-BA-3-33, 10-BA-4-24, BWR-1, BWR-22, and BWR-23) of tomato and identified genome-wide single nucleotide polymorphisms (SNPs) in resistant and susceptible groups of cultivars ( Kim et al 2018 ). The highest number of polymorphic SNPs in coding regions were found on chromosome 12 (168 SNPs) followed by chromosome 6 (53 SNPs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation